CDCA7 promotes TGF‐β‐induced epithelial–mesenchymal transition via transcriptionally regulating Smad4/Smad7 in ESCC. Issue 1 (14th November 2022) - Li, Hongyi; Wang, Shaojie; Li, Xiubo; Weng, Yongjia; Guo, Dinghe; Kong, Pengzhou; Cheng, Caixia; Wang, Yanqiang; Zhang, Ling; Cheng, Xiaolong; Cui, Yongping
Abstract: Cell division cycle associated 7 ( CDCA7 ) is a copy number amplification gene that contributes to the metastasis and invasion of tumors, including esophageal squamous cell carcinoma (ESCC). This present study aimed at clarifying whether high expression of CDCA7 promotes the metastasis and invasion of ESCC cell lines and exploring the underlying mechanisms implicated in epithelial–mesenchymal transition (EMT) of ESCC. The role of CDCA7 in the regulation of ESCC metastasis and invasion was evaluated using ESCC cell lines. Expression of EMT‐related markers including E‐cadherin, N‐cadherin, Vimentin, Snail, and Slug, transforming growth factor β (TGF‐β) signaling pathway including Smad2/3, p‐Smad2/3, Smad4, and Smad7 were detected in CDCA7 knockdown and overexpressed cell lines. Dual‐luciferase reporter assay and rescue assay were used to explore the underlying mechanisms that CDCA7 contributed to the metastasis and invasion of ESCC. High CDCA7 expression significantly promoted the metastasis and invasion of ESCC cell lines both in vivo and in vitro. Additionally, the expression of CDCA7 positively correlated with the expression of N‐cadherin, Vimentin, Snail, Slug, TGF‐β signaling pathway and negatively correlated with the expression of E‐cadherin. Furthermore, CDCA7 transcriptionally regulated the expression of Smad4 and Smad7. Knockdown of CDCA7 inhibited the TGF‐β signaling pathway and therefore inhibited EMT. Our data indicated that CDCA7 was heavily involved in EMT by regulating the expression of Smad4 and Smad7 in TGF‐β signaling pathway. CDCA7 might be a new therapeutic target in the suppression of metastasis and invasion of ESCC. Abstract : High cell division cycle associated 7 (CDCA7) expression significantly promoted the metastasis and invasion of esophageal squamous cell carcinoma cell lines both in vivo and in vitro. The expression of CDCA7 positively correlated with the expression of N‐cadherin, Vimentin, Snail, Slug, transforming growth factor β signaling pathway and negatively correlated with the expression of E‐cadherin. CDCA7 transcriptionally regulated the expression of Smad4 and Smad7